2020
DOI: 10.1109/tmbmc.2020.3012874
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multi-Chemical Transmission in the Macro-Scale

Abstract: Molecular communications (MC) offers an alternative to established methods (i.e., electromagnetic waves), in areas where the latter might prove ineffective (e.g., underwater or underground) due to the environment's effect on the transmitted signal. In such environments the use of particle (i.e., chemical) based communication may offer a better solution. One of the unique attributes of MC is its ability to employ chemicals as messengers, and transmitting multiple chemicals concurrently offers the potential to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, controlled experiments of chemical communication via a gaseous medium with a single chemical and with two chemicals were reported in Refs. [29,30]. The latter studies also demonstrated that the chemical communication links can indeed be described by diffusion-advection models.…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, controlled experiments of chemical communication via a gaseous medium with a single chemical and with two chemicals were reported in Refs. [29,30]. The latter studies also demonstrated that the chemical communication links can indeed be described by diffusion-advection models.…”
Section: Introductionmentioning
confidence: 77%
“…In the following years, many different types of testbeds have been proposed, which can be associated with different disciplines in science and technology. The testbeds can be classified as macro-scale (e.g., [13]) and micro-scale (e.g., [14]) and at the micro-scale a distinction can be made between biological (e.g., [15]) and non-biological (e.g., [16]) setups. A comprehensive overview of MC testbeds can be found in [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the following years, many different types of testbeds have been proposed, which can be associated with different disciplines in science and technology. The testbeds can be classified as macro-scale (e.g., [13]) and micro-scale (e.g., [14]) and at the micro-scale a distinction can be made between biological (e.g., [15]) and non-biological (e.g., [16]) setups. A comprehensive overview of MC testbeds can be found in [17], [18].…”
Section: Introductionmentioning
confidence: 99%